Determinants Of Agricultural Output In Cambodia, 1993-2015 - Kanyi, Eing (2018)
Agriculture in Cambodia has been playing an essential role in the national income and production for the past few decades. Nevertheless, the continuous decline in the level of GDP contribution of agricultural output has sparked interest on how to re-improve the contribution of this sector given the fact that Cambodia has just joined the lower-middle income group levels. We believe that the agricultural sector should still be given priority alongside the manufacturing sector for the next few decades of the economic development strategy in Cambodia.